História e cinema: reflexões sobre a escravidão no filme Harriet (2019) - Silva, Milenna Fernandes da (Universidade Federal do Tocantins, 2024)
Slavery will always be a subject of discussion in History, as it manages to reach unprecedented fields, expanding the knowledge of History. The objective of the research is to work with the theme based on the film Harriet, produced in 2019; a cinematographic work that deals with slavery. To do this, we draw a relationship between History and Cinema, turning the film into a source for the historiographic field. The methodology applied addresses theoretical studies on the use of cinema in the classroom as a pedagogical resource in the classroom. The research contribution seeks to explore the theme of slavery through the film in the light of History.